Treat Iron-Related Childhood-Onset Neurodegeneration (TIRCON)—An International Network on Care and Research for Patients With Neurodegeneration With Brain Iron Accumulation (NBIA) - Karin, Ivan; Büchner, Boriana; Gauzy, Florence; Klucken, Angelika; Klopstock, Thomas (Frontiers in Neurology, 2021)
In order to improve clinical care, coordinate research activities and raise awareness for the ultra-orphan Neurodegeneration with Brain Iron Accumulation (NBIA) disorders, a group of NBIA clinicians and researchers, industry partners and patient advocacies from six European countries, Canada and the US joined forces in 2010 to set-up the collaborative initiative TIRCON (Treat Iron-Related Childhood-Onset Neurodegeneration). As a research project, TIRCON received funding in the 7th Framework Programme (FP7) of the European Union (EU) from 2011 to 2015. After successful and timely completion of the initial FP7 project, funding and donations from industry and patient organizations have sustained the further development of TIRCON's dedicated clinical research infrastructure and its governance architecture, as well as the ongoing efforts undertaken in the NBIA community to establish a network of care. From the beginning, the University Hospital of the Ludwig-Maximilians-University in Munich, Germany has been coordinating the TIRCON initiative. It consists of 8 work packages, of which the first double-blind, placebo-controlled, randomized, multi-site clinical trial in NBIA (deferiprone in PKAN, completed) and a global patient registry and biobank, currently comprising baseline and follow-up data of > 400 NBIA patients have gained particular importance. Here we describe TIRCON's history with all the challenges and achievements in diagnosing and treating NBIA. Today, TIRCON lays the ground for future clinical care and research. In these times, it may also serve as a good example of well-directed governmental funding and fruitful international scientific collaboration.